Dyshidrotic eczema in two patients on secukinumab for plaque psoriasis: A case report. (February 2020) - Bose, Reetesh; Beecker, Jennifer
Secukinumab was the first fully human anti-interleukin-17a monoclonal antibody and successfully treated moderate-severe psoriasis. These new, targeted, medications are becoming more ubiquitous, but long-term side effects are not fully known. Post-market surveillance is crucial to identify delayed adverse events, analogous to the paradoxical development of pustular psoriasis in a subset of patients treated with the anti-tumor necrosis factor-alpha class drugs. Dyshidrotic eczema and pompholyx are rare variants of dermatitis characterized by vesicles or bullae on the palms, soles and sides of the fingers. The etiology of dyshidrotic eczema is not always known, but medications have been implicated in a minority of patients. Herein, we present two cases of dyshidrotic eczema developing in patients on secukinumab for psoriasis. Extended follow-up and larger numbers of patients are needed to fully understand the potential association between secukinumab and dyshidrotic eczema.